Strength of Concrete Produced With Recycled Materials - Ali, Mohamed Emad (2019)
A Master of Science thesis in Civil Engineering by Mohamed Emad Ali entitled, “Strength of Concrete Produced with Recycled Materials”, submitted in December 2019. Thesis advisor is Dr. Sherif Yehia and thesis co-advisor is Dr. Farid Abed. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).